Abnormal suppression of arginine-vasopressin by clonidine in multiple system atrophy - Kimber, J.; Watson, L.; Mathias, C. J. (Clinical autonomic research, 1999)
In normal man, the centrally active alpha2-adrenoceptor agonist clonidine reduces arginine-vasopressin (AVP) secretion, probably by presynaptic inhibition of noradrenergic neuron terminals in the supraoptic nucleus. A lesion of noradrenergic pathways in animals abolishes this response to clonidine. At postmortem in multiple system atrophy (MSA) there is marked loss of hypothalamic noradrenergic innervation. We hypothesized that the AVP response to clonidine in MSA may be abnormal and therefore studied the AVP response to clonidine (2 microg/ kg iv) in 10 subjects with MSA and compared them to six healthy age-matched control subjects. Basal levels of AVP were similar in controls and MSA. Following clonidine there was a significantly greater fall in controls than MSA (-47 +/- 4% vs -25 +/- 6%; p < 0.05). There was a similar fall in mean arterial pressure (MAP) and plasma catecholamines in both groups, with no change in plasma osmolarity, excluding these as a contributary factor. In conclusion, there is an abnormal AVP response to clonidine in MSA, which probably represents loss of functional noradrenergic innervation of the supraoptic nucleus.